E Efektivitas LKPD Berbasis Problem-Based Learning dalam Meningkatkan Literasi Matematis Peserta Didik Madrasah Ibtidaiyah - Novitaningrum, Diah Tri; Mala, Asnal; Sasmita, Febriarsita Eka (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2025)
This study was conducted to examine the effectiveness of Problem-Based Learning (PBL)-based Student Worksheets (LKPD) in improving mathematical literacy among fourth-grade students at MI Darul Ulum Tambak Rejo Waru Sidoarjo. The research followed a quantitative approach with a quasi-experimental design, involving a control and an experimental group. The development of the LKPD used the ADDIE model, consisting of five stages: analysis, design, development, implementation, and evaluation. The LKPD was considered effective if it met three main criteria: realistic, useful, and thoughtful. Data were collected through pre-test and post-test scores and student questionnaires to evaluate both learning outcomes and the practicality of the worksheets. The results showed that the experimental group had a significant increase in mathematical literacy scores, from a pre-test average of 52.35 to a post-test average of 82.94. In comparison, the control group improved from 52.27 to 75.45. The practicality level of the LKPD, based on student responses, reached 83.30%, indicating positive reception despite some students perceiving it as monotonous. These findings demonstrate that PBL-based LKPD is not only effective in enhancing students’ mathematical literacy but also practical for classroom use. The study contributes valuable insights for teachers and future researchers in developing high-quality, efficient learning materials tailored to elementary mathematics education. It also supports the long-term implementation of PBL strategies in madrasah settings to foster deeper understanding and engagement in mathematics learning.